Determinants of Islamic Commercial Bank Stability in Indonesia during the 2019–2024: A Fixed Effects Panel Model with Driscoll–Kraay Standard Eror Approach - Muhammad Fakhri Dzulfiqar; Fira Nurafini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Stability in the banking sector is essential for maintaining financial system resilience, particularly in the context of Islamic finance. This study aims to examine the effects of internal and external factors on the stability of Islamic commercial banks in Indonesia over the 2019–2024 period. Secondary data were obtained from the Financial Services Authority (OJK) and the Central Bureau of Statistics (BPS). The sample comprises ten Islamic commercial banks selected via purposive sampling. The analysis was carried out using panel‐data regression with Driscoll–Kraay standard errors to correct for heteroskedasticity, and serial correlation. Findings indicate that financial performance indicators, BOPO, NPF, NOM, and CAR significantly affect bank stability, whereas the FDR does not significant. Among macroeconomic factors, inflation and HHI exert significant effects, while GDP growth and exchange-rate remain insignificant to Islamic Commercial Banking.